2019
DOI: 10.21037/atm.2019.05.65
|View full text |Cite
|
Sign up to set email alerts
|

Stability evaluation of anterior external fixation in patient with unstable pelvic ring fracture: a finite element analysis

Abstract: Background: The pelvic ring fractures (PRF) are commonly induced by the high-energy impact and will lead to unstable and sever injures. This study is aimed to explore the stability of anterior external fixation in treating pelvis fracture and evaluate the possibility for these kinds of patients to reduce bedridden time.Methods: A patient with Tile B3 pelvis fracture was chosen in the research and the corresponding digital model was reconstructed according to the CT images and 3D scanning. Four angles of pelvis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Lateral stress may lead to internal fixation failure following fracture surgery; hence, it is best to avoid lateral lying after surgery. In addition, Lan Li et al analyzed the mechanical environment at 30°, 60°, and 90° in semi-recumbency after pelvic fracture surgery, and the results showed that the fracture displacement of patients seated at 90° was small and that there was no substantial mechanical concentration [ 12 ]. Therefore, we expect that patients with Tile B2 pelvic fracture can perform standing and sitting activities until the fracture heals within 3 months of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lateral stress may lead to internal fixation failure following fracture surgery; hence, it is best to avoid lateral lying after surgery. In addition, Lan Li et al analyzed the mechanical environment at 30°, 60°, and 90° in semi-recumbency after pelvic fracture surgery, and the results showed that the fracture displacement of patients seated at 90° was small and that there was no substantial mechanical concentration [ 12 ]. Therefore, we expect that patients with Tile B2 pelvic fracture can perform standing and sitting activities until the fracture heals within 3 months of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the simulated standing position, the model constrained six degrees of freedom of the two-sided acetabulum and applied a vertical downward load of 600 N to the upper surface of the sacrum to simulate the upper body weight ( Figure 2 A). In the simulated standing and sitting position, the model constrained six degrees of freedom of two-sided ischial tuberosity and applied a vertical downward load of 600 N to the upper surface of the sacrum ( Figure 2 B) [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is also reported in a large number of patients with multiple trauma (1). It is due to high-energy trauma, which is associated with damage to other organs, like chest and abdomen (2).…”
Section: Introductionmentioning
confidence: 97%
“…Unstable posterior pelvic ring injuries (UPPRI) usually result from violent high-impact injuries (1)(2)(3). They are associated with high morbidity and mortality due to iatrogenic injury to anatomically contiguous structures and the prolonged patient immobilization that is often required in the event of complications (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Original Article good treatment efficacy is a key surgical imperative that can help minimize complications and the duration of immobilization. Conservative treatment outcomes have been largely disappointing1, and are often associated with long-term sequelae such as chronic pain and an inability to walk normally (2,3).…”
Section: Introductionmentioning
confidence: 99%